Beswitched - Saunders, Kate, 1960- (Yearling, 2012)
On her way, reluctantly, to a boarding school in present-day England, Flora suddenly finds herself in 1935, the new girl at St. Winifred's, having been summoned via a magic spell by her new dormitory mates.